The Role of Discrimination Experiences in Postrape Adjustment Among Racial and Ethnic Minority Women. Issue 19 (October 2022) - Walsh, Kate; Gilmore, Amanda K.; Barr, Simone C.; Frazier, Patricia; Ledray, Linda; Acierno, Ron; Ruggiero, Kenneth J.; Kilpatrick, Dean G.; Resnick, Heidi S.
Although recent studies have linked discrimination frequency among Black and Latinx individuals to PTSD symptom severity, to our knowledge, these associations have yet to be examined among a diverse sample of recent rape survivors. The current secondary analysis of existing data examined the role of discrimination experiences in post-traumatic stress disorder (PTSD) symptoms, depression, and alcohol and drug problems among a racially and ethnically diverse sample of recent rape survivors. Participants were 139 Black (48.2%; n = 67), American Indian (18.7%; n = 26), Hispanic (15.1%; n = 21), and mixed race (17.3%; n = 24) girls and women age 15 or older who presented to the emergency department (ED) for a sexual assault forensic medical exam. They were randomly assigned to one of three intervention conditions, and completed a six-month postrape follow-up, including questions about mental health, substance use problems, and discrimination experiences. Regression analyses revealed that Black women experienced discrimination in significantly more situations and with greater frequency compared to American Indian and Hispanic women. Discrimination frequency was positively associated with PTSD and depression symptoms even after controlling for age, education, race, and intervention condition, but was not associated with alcohol or drug problems. Findings highlight the importance of attending to the heterogeneous experiences of discrimination among racial and ethnic minority women. Future work should adapt evidence-based early interventions to be maximally effective at combating both racial and sexual trauma exposures.